Enhancement of efferocytosis through biased FPR2 signaling attenuates intestinal inflammation - Ming‐Yue Wu; Yun‐Jun Ge; Er‐Jin Wang; Qi‐Wen Liao; Zheng‐Yu Ren; Yang Yu; Guoyuan Zhu; Chun‐Ping Liu; Meng‐Ni Zhang; Huanxing Su; Han‐Ming Shen; Ye Chen; et al. (EMBO Molecular Medicine)
Abstract Efficient clearance of dying cells (efferocytosis) is an evolutionarily conserved process for tissue homeostasis. Genetic enhancement of efferocytosis exhibits therapeutic potential for inflammation resolution and tissue repair. However, pharmacological approaches to enhance efferocytosis remain sparse due to a lack of targets for modulation. Here, we report the identification of columbamine (COL) which enhances macrophage‐mediated efferocytosis and attenuates intestinal inflammation in a murine colitis model. COL enhances efferocytosis by promoting LC3‐associated phagocytosis (LAP), a non‐canonical form of autophagy. Transcriptome analysis and pharmacological characterization revealed that COL is a biased agonist that occupies a part of the ligand binding pocket of formyl peptide receptor 2 (FPR2), a G‐protein coupled receptor involved in inflammation regulation. Genetic ablation of the Fpr2 gene or treatment with an FPR2 antagonist abolishes COL‐induced efferocytosis, anti‐colitis activity and LAP. Taken together, our study identifies FPR2 as a potential target for modulating LC3‐associated efferocytosis to alleviate intestinal inflammation and highlights the therapeutic value of COL, a natural and biased agonist of FPR2, in the treatment of inflammatory bowel disease.